2014
DOI: 10.1007/s10549-014-3102-8
|View full text |Cite
|
Sign up to set email alerts
|

Abrogating phosphorylation of eIF4B is required for EGFR and mTOR inhibitor synergy in triple-negative breast cancer

Abstract: Purpose Triple negative breast cancer (TNBC) patients suffer from a highly malignant and aggressive disease. They have a high rate of relapse and often develop resistance to standard chemotherapy. Many TNBCs have elevated epidermal growth factor receptor (EGFR) but are resistant to EGFR inhibitors as monotherapy. In this study we sought to find a combination therapy that could sensitize TNBC to EGFR inhibitors. Methods Phospho-mass spectrometry was performed on the TNBC cell line, BT20, treated with 0.5 μM g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
25
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 35 publications
4
25
2
Order By: Relevance
“…In addition, the expression levels of EGFR, HER2 and HER3 were determined in primary tumors of colorectal cancer cells, and corresponded with lymph node metastases and liver metastases (42,43). The dysregulation of human EGFR pathways by the overexpression or constitutive activation promote s tumor processes, angiogenesis and metastasis in several types of human cancer (4)(5)(6)(7)(8)(9)(10)(11)(12)(13). Previous studies have demonstrated that tetrandrine inhibits cell metastasis in 4T1 breast cancer cells (18) and CT26 colorectal cancer cells in vivo (25).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the expression levels of EGFR, HER2 and HER3 were determined in primary tumors of colorectal cancer cells, and corresponded with lymph node metastases and liver metastases (42,43). The dysregulation of human EGFR pathways by the overexpression or constitutive activation promote s tumor processes, angiogenesis and metastasis in several types of human cancer (4)(5)(6)(7)(8)(9)(10)(11)(12)(13). Previous studies have demonstrated that tetrandrine inhibits cell metastasis in 4T1 breast cancer cells (18) and CT26 colorectal cancer cells in vivo (25).…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal protein activity and/or expression levels of EGFR have been correlated with the etiology of several types of human cancer, including colorectal cancer (4,5), non-small cell lung cancer (6,7), breast cancer (8,9), head and neck squamous cell carcinoma (10,11), pancreatic cancer (12) and brain cancer (13). EGFR-targeted therapy has been validated in human colorectal cancer (14), and the chemotherapeutics include pharmacological agents, including cetuximab (Erbitux), which is an EGFR inhibitor (15).…”
Section: Introductionmentioning
confidence: 99%
“…TiO 2 techniques are usually performed using self-packed or commercial products with microcolumn, 17,56 or beads. 20,25,40 To improve the reproducibility of TiO 2 for phosphopeptide enrichment, Tape and co-worker described that the automatic phosphopeptide enrichment using magnetic TiO 2 beads with IMAC. 40 The automated enrichment system with magnetic TiO 2 beads is achieved by controlling 96-well plates at the eight carousel positions.…”
Section: Titanium Dioxide (Tio 2 )mentioning
confidence: 99%
“…59 In many reports, acidic loading buffers on TiO 2 have been tested and optimized with the modifiers including 2, 5-dihydroxybenzoic acid (DHB), malic acid, lactic acid, and other acidic reagents to enhance the enrichment efficiency of phosphopeptide. [17][18][19][20][21] Capacity of acidic modifier in loading buffer for removing non-specific binding decreased as follows: DHB = salicylic acid = phthalic acid > benzoic acid = cyclohexanecarboxylic acid > phosphoric acid > TFA > acetic acid. 53 In recently, specificity of TiO 2 chromatography was optimized by adding glycerol 60 or citric acid.…”
Section: Titanium Dioxide (Tio 2 )mentioning
confidence: 99%
See 1 more Smart Citation